The Use of Listen-Read-Discuss (LRD) Strategy in Enhancing Students’ Reading Comprehension - Warta, I Ketut; Ari Wiryadi Joni, Dewa Ayu; Krismayani, Ni Wayan (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Mahasaraswati Denpasar, 2023)
The objective of the present study was to find out whether the reading comprehension of the students of SMA (SLUA) Saraswati 1 Denpasar could be improved through Listen-Read-Discuss Strategy. The researcher administered three research instruments, namely pre-test, post-tests and questionnaire. The students' means score showed a significant improvement from the pre-test was 63.5 to 73.3 in cycle I and 81.3 in cycle II. Furthermore, to collect the additional data, the researcher administered the questionnaire at the end of cycle II. It showed that the students responded positively which showed the percentage of 46.59% strongly agreed, 52.72% agreed, 0.68% undecided, 0% disagreed and 0% strongly disagreed. Based on the results of this study, it could be concluded that the Listen-Read-Discuss Strategy could improve the students’ reading comprehension of students of SMA (SLUA) Saraswati 1 Denpasar.